Patient and physician treatment preferences in relapsed/refractory follicular lymphoma: a discrete choice experiment in the United States, United Kingdom, France, Germany, Brazil, and Japan - Gribben, John G.; Bachy, Emmanuel; Ray, Markqayne; Krupsky, Kathryn; Beusterien, Kathleen; Kopenhafer, Lewis; Beygi, Sara; Best, Timothy; Ball, Graeme; Will, Oliver; Palivela, Madhu; Patel, Anik; et al. (Frontiers in Oncology, 2025)
IntroductionThe objectives of this study were to identify key treatment attributes that drive physician and patient preferences for second line (2L) and third line (3L) treatments in relapsed/refractory (R/R) follicular lymphoma (FL).MethodsA multi- country, internet-based survey was administered to patients(N=195) with R/R FL and treating physicians (N=300) from the United States, United Kingdom, France, Germany, Brazil, and Japan. The survey included two discrete choice experiments – one for 2L and one for 3L treatment options – that prompted respondents to select their preferred option between two hypothetical treatment profiles varying on seven attributes associated with treatment for R/RFL: progression-free survival (PFS), overall survival (OS), serious adverse events (AE), cytokine release syndrome (CRS) events, neurological events, fatigue, and administration. Mean preference weights and relative attribute importance were estimated in each sample, overall and by country, using hierarchical Bayesian models. Physician estimates were also stratified by practice setting.ResultsTreatment preferences for physicians and patients were most influenced by PFS. Beyond PFS, patients placed greater emphasis on the administration of medications, whereas physicians tended to focus more on five-year OS and toxicity profiles of agents. Preference for PFS above all other 2L and 3L treatment attributes was consistent for physicians, regardless of practice setting and country. However, patient treatment preferences varied by country.DiscussionThese results offer key perspectives on how physicians and patients evaluate treatment options in 2L and 3L treatment settings; this information is essential for facilitating shared decision-making in an expanding, complex treatment landscape.